RPC-based frequency control strategy of LCC-HVDC sending end power system with renewable energy - Wei, Peng; Chai, Bin; Shi, Lei; Shi, Qiaoming; Liu, Ruopeng; Wang, Yongping; Liu, Kai (Frontiers in Energy Research, 2022)
Long-distance transmission of renewable energy via DC is currently a more economical transmission scheme. As the proportion of renewable energy at the generation end continues to rise, the inertia and damping level of the system is reduced, causing serious frequency-related issues. This paper first analyzes the working principle and control method of the LCC-HVDC system, summarizes the frequency control methods of the sending end power grid and their existing problems, and proposes a frequency control scheme for the LCC-HVDC sending end system based on the concept of rapid power compensation (RPC). Finally, the LCC-HVDC system model integrated with the large-capacity wind farm and thermal power plant is built in MATLAB/Simulink. Under conditions of load power fluctuation and sudden wind speed change, the proposed strategy fully utilizes the spare capacity of the system, effectively improves the frequency indexes of the system, and improves the frequency characteristics of the renewable energy sending end grid.